2008
DOI: 10.1053/j.ajkd.2008.02.363
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-Hip Ratio, Body Mass Index, and Subsequent Kidney Disease and Death

Abstract: Background-Chronic kidney disease (CKD) and obesity are important public health concerns. We examined the association between anthropomorphic measures and incident CKD and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
164
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(184 citation statements)
references
References 28 publications
12
164
1
7
Order By: Relevance
“…The consequence of abdominal adiposity in relation to kidney function impairment has been little documented and it is a noteworthy subject, considering its frequent association with hypertension and diabetes, which are the main causes of CKD in the world. Some studies have shown an association between the central distribution of fat, measured by the WHR, with hypertension 14,27 , microalbuminuria 28 and CKD 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of abdominal adiposity in relation to kidney function impairment has been little documented and it is a noteworthy subject, considering its frequent association with hypertension and diabetes, which are the main causes of CKD in the world. Some studies have shown an association between the central distribution of fat, measured by the WHR, with hypertension 14,27 , microalbuminuria 28 and CKD 29 .…”
Section: Discussionmentioning
confidence: 99%
“…107 Because the metabolically more active visceral fat depots are the key factor in the development of insulin resistance, hypertension, fatty liver, type 2 diabetes, and atherosclerosis, 46 nephrologists should estimate fat distribution. Indeed, the gene expression differs markedly between visceral and subcutaneous fat depots, 108 and studies in the general population 109 and CKD 110 and dialysis patients 111 show that increased WC (or WHR) was related to a higher risk of death from major specific causes independent of BMI. In accordance, visceral obesity is linked to inflammation, protein energy wasting, and worse outcome in hemodialysis patients.…”
Section: Should Nephrologists Promote Weight Gain In Dialysis Patients?mentioning
confidence: 99%
“…[1][2][3] This increased risk is often attributed to associated conditions, such as weight excess, hypertension, dyslipidemia, and diabetes. [4][5][6][7][8][9][10] However, after adjustment for these conditions, central body fat distribution, estimated from waist-to-hip ratio (WHR), remains an independent determinant of increased long-term renal risk.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10] However, after adjustment for these conditions, central body fat distribution, estimated from waist-to-hip ratio (WHR), remains an independent determinant of increased long-term renal risk. [1][2][3] The mechanisms underlying this increased renal risk in association with a central body fat distribution are not well established. Small studies suggest that central body fat distribution is associated with an unfavorable renal hemodynamic profile; 11,12 however, these studies did not control for concomitant presence of overall weight excess as commonly reflected by body mass index (BMI), a well established determinant of an unfavorable renal hemodynamic profile in itself.…”
mentioning
confidence: 99%